1971
DOI: 10.1002/bjs.1800581113
|View full text |Cite
|
Sign up to set email alerts
|

Complete prolapse of the rectum a report on 140 cases treated by rectopexy

Abstract: Indirect fixation of the rectum to the anterior ongitudinal ligament over the sacral promontory was performed at 146 operations for procidentia recti in a homogeneous series of 140 patients. Before fixation the rectum was widely dissected and thoroughly mobilized. The recurrence rate after follow‐up intervals of up to 15 years was 3.6 per cent. The procedure is simple to perform and eliminates the hazard of anastomotic breakdown which is associated with excisional methods. The authors regard it as the method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…Three major techniques are used: posterior mesh rectal fixation (Wells technique or Ripstein technique), or the ventral rectal fixation using a double anterolateral mesh (Orr-Loygue technique). 6 Both approaches have proved to induce postoperative constipation. 1,2,[7][8][9][10] Although this complication is multifactorial, it has been associated with rectal denervation and fibrosis of the rectal walls after extensive dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Three major techniques are used: posterior mesh rectal fixation (Wells technique or Ripstein technique), or the ventral rectal fixation using a double anterolateral mesh (Orr-Loygue technique). 6 Both approaches have proved to induce postoperative constipation. 1,2,[7][8][9][10] Although this complication is multifactorial, it has been associated with rectal denervation and fibrosis of the rectal walls after extensive dissection.…”
Section: Discussionmentioning
confidence: 99%
“…It can be hypothesized that IRP is a precursor stage of ERP. In ERP, resectional therapy has been shown to have high recurrence rates in contrast to rectopexy [2023]. If we extrapolate this to the results after LVR and STARR in the treatment of IRP, it is perhaps reasonable to expect a better long-term outcome after LVR.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding genital prolapse, many of the corrective surgical procedures, whether transvaginal or transabdominal, are optional 1,6–12 and should be selected according to the specific problem, as noted on pelvic examination, and the presence or absence of the uterus 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In a later work, Tancer et al 6 found it remarkable that the world gynaecological literature of the last 50 years had provided almost no evidence that genital and rectal prolapse can be concurrent. Yet, colorectal surgeons have been aware of this phenomenon since the 1970s 1,7–12 …”
Section: Introductionmentioning
confidence: 99%